A test of French phonology: construction and use - Bérubé, Daniel; Bernhardt, B. May; Stemberger, Joseph P. (Canadian Journal of Speech-Language Pathology & Audiology, 2015)
Abstract: Clinicians have had limited resources for conducting phonological evaluations of Canadian Francophone children and, to this day, there are no standardized tests of French-Canadian phonology (Brosseau-Lapre, Rvachew, Arcand, & Leroux, 2011). Recently, preliminary normative data were collected with a French screening tool in Quebec, with results indicating that the screening tool is sensitive in identifying children with protracted phonological development (MacLeod, Sutton, Sylvestre, Thordardottir, & Trudeau, 2014). The current paper presents another new assessment tool for Canadian French phonology (developed for Manitoba French) to evaluate the segments and word structures of Canadian French phonology in depth within the context of a nonlinear phonological framework. The objectives of this article are: (a) to provide an overview of nonlinear phonology, and demonstrate how models of linear and nonlinear phonology account for non-adjacent segments, (b) to describe Manitoba French phonology, (c) to examine the phonological characteristics of the French word list (consonants, vowels, and word structures), and (d) to explain briefly how to administer, transcribe, and analyze data from the assessment tool. Abrégé: Les orthophonistes ont peu d'options pour l'evaluation phonologique du francais canadien chez les enfants et a ce jour il n'y a encore aucun test norme pour ce type d'evaluation (BrosseauLapre, Rvachew, Arcand, & Leroux, 2011). Recemment, une collecte de donnees preliminaires a ete effectuee aupres des enfants francophones au Quebec avec un outil francais de depistage de la phonologie et les resultats indiquent que l'outil est sensible pour identifier des enfants ayant des troubles de la phonologie (MacLeod, Sutton, Sylvestre, Thordardottir, &Trudeau, 2014). Ce rapport-ci presente un nouvel outil pour l'evaluation detaillee de la phonologie pour le francais canadien (elabore pour le francais du Manitoba), dont la structure vise a couvrir l'inventaire complet des phonemes et des structures de mots du francais canadien, dans le cadre theorique de la phonologie non lineaire. Les objectifs du rapport sont : (a) de presenter un survol de la phonologie non lineaire et demontrer comment les modeles de phonologie lineaire et non lineaire expliquent les phenomenes impliquant des segments non adjacents, (b) de decrire, brievement, la phonologie du francais Manitobain, (c) d'examiner les caracteristiques phonologiques de la liste de mots francais (les consonnes, les voyelles, et les structures du mot) et (d) d'expliquer brievement comment administrer, transcrire et analyser les donnees du test.

A comparison of two phonological screening tools for French-speaking children - Bérubé, Daniel; Macleod, Andrea A. N. (International Journal of Speech-Language Pathology, 2022)
Purpose: To examine two screening tools for phonological production, the Evaluation Sommaire de la Phonologie chez l’enfant d’âge préscolaire (ESPP) and the Test de Phonologie du Français Canadien-Dépistage (TPFC-D), developed according to differing theoretical perspectives. The TPFC-D, designed according to nonlinear phonology, includes more words and contains a greater variety of segments across word structure as compared to the ESPP, which was guided by a linear phonological framework. The greater response rate to test items, time of administration, and phonological complexity were expected on the TPFC-D. Method: Each screening tool was administered to 14 4-year-old French-speaking children living in Central Canada. Paired samples t-tests compared children’s responses on the two tasks with regards to (a) response rate and time of administration, (b) an overall percentage of consonants correct (PCC) and percentage of vowel correct (PVC), and (c) complexity of productions (i.e. PCC and PVC in relation to word structure, Word Shape Match, Whole Word Match, Phonological Mean Length of Utterance (pMLU) and Proportion of Whole-Word Proximity). Result: Item response rates were higher for the TPFC-D whereas time of administration, PCC and PVC were similar for both the ESPP and TPFC-D. Complexity measures showed a higher proportion of deletions in clusters and higher pMLUs on the TPFC-D compared to the ESPP. Conclusion: Both screening measures are appropriate for speech-language pathologists who want to assess quickly pre-school-aged children. Since the TPFC-D is phonologically more complex, it is recommended for clinicians needing to screen children who likely present with multiple speech sound errors across their phonological system.

Recrutement de prestataires de services maîtrisant le français : conseils et stratégies - Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (2023)
Le présent rapport a été conçu en tant que ressource pour aider l’"Équipe santé Enfants avant tout" à élaborer une stratégie de recrutement, de maintien en poste et de formation des ressources humaines dans la région sanitaire de Champlain, en Ontario. Le rapport a été préparé par l’Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (« l’Institut du savoir »). L’Institut du savoir crée des liens, transmet des connaissances et tire parti de son expertise pour améliorer les compétences des prestataires de services directs et des organismes de l’Ontario afin de renforcer les programmes et les services de santé mentale de l’Ontario pour tous les enfants, les jeunes, les familles et les prestataires de soins. Nous voulions savoir ce que font les organismes — particulièrement ceux du secteur de la santé — pour recruter des prestataires de services qui maîtrisent le français. Nous voulions aussi nous renseigner sur les pratiques de recrutement fondées sur des données probantes décrites dans la littérature. Les stratégies et les principes directeurs présentés dans cette ressource sont tirés d’une analyse contextuelle qui comprenait un examen rapide et non systématique de la littérature. De plus, nous avons consulté des intervenant.e.s clés et des leaders dans le domaine qui ont une expérience directe de recrutement de prestataires de services qui maîtrisent le français.

Recruiting service providers with French proficiency: Tips and strategies - The Knowledge Institute on Child and Youth Mental Health and Addictions (2023)
This report is designed as a resource to support the "Kids Come First Health Team" in developing a strategy for recruiting, retaining and training human resources in Ontario’s Champlain health region. The report has been prepared by the Knowledge Institute on Child and Youth Mental Health and Addictions (the Knowledge Institute). The Knowledge Institute builds connections, shares knowledge and draws on expertise to enhance the skills of direct service providers and agencies across Ontario in order to strengthen Ontario’s mental health programs and services for all children, young people, families and caregivers. We wanted to discover what organizations are doing — particularly organizations in the health sector — to recruit service providers with French proficiency. We also wanted to learn about evidence-based practices for recruitment from the literature. The strategies and guiding principles provided in this resource were derived from an environmental scan that included a rapid, nonsystematic literature review. As well, we consulted with key stakeholders and leaders in the field who have direct experience with recruiting service providers with French proficiency.

Bottin des ressources en petite enfance à Iqaluit, Nunavut - youth primary health care (2020)
Ce bottin vise à aider les parents de jeunes enfants et les intervenants à avoir accès rapidement aux ressources pertinentes à la petite enfance qui sont disponibles à Iqaluit. Ce bottin présente une recension exhaustive de ces ressources en spécifiant le niveau d’accès aux services en français. Par ressources, on entend ici les services, les programmes, les ressources éducatives et autres sources d’information pertinente pour les périodes pré et péri natales, ainsi que pour les familles avec enfants de 0 à 6 ans.